# Find an equation for the line that passes through the points (−5,-3) and (3, 3)?

### 8 Answers

- Engr. RonaldLv 71 month agoFavorite Answer
solving for the slope

m = (y₂ - y₁ )/(x₂ - x₁)

m = [3 - (-3)]/[3 - (-5)]

m = (3 + 3)/(3 + 5)

m = 6/8 or 3/4

apply point slope form

y - y₁ = m(x - x₁)

y - (-3) = 3/4[x - (-5)]

y + 3 = 3/4(x + 5)

4(y + 3) = 3(x + 5)

4y + 12 = 3x + 15

4y = 3x + 15 - 12

4y = 3x + 3

y = 3/4x + 3/4 answer//

The equation of the line is y = 3/4x + 3/4

- Login to reply the answers

- lenpol7Lv 71 month ago
y- - 3 = (3--3)/(3--5)(x - -5)

y + 5 = (6)/(8)(x + 5)

y + 5 = )3/4)(x + 8)

y + 5 = 3x/4 + 24/4

y = 3x/4 + 6 - 5

y = 3x/4 + 1

or

4y = 3x + 4

or

4y -3x = 1

or

4y - 3x - 1 = 0

- Login to reply the answers

- PhilipLv 61 month ago
A(-5,-3), B(3,3). Slope AB = (3+3)/(3+5) = (3/4).

Let line L: y = (3/4)x + b...(1). B is on L. Therefore

3 = (3/4)3 +b, ie., b =3[1-(3/4)] = 3(1/4) = (3/4).

Then L: y = (3/4)x + (3/4) {slope, y-intercept} or

L: 3x -4y +3 = 0 {standard}.

- Login to reply the answers

- DavidLv 71 month ago
Points: (-5, -3) and (3, 3)

Slope: 3/4 or 0.75

Equation: y = 0,75x +0.75

- Login to reply the answers

- How do you think about the answers? You can sign in to vote the answer.
- MyRankLv 61 month ago
A(-5, -3), B(3, 3)

y - y₁ = y₂-y₁/x₂-x₁ (x-x₁)

y-(-3) = 3-(-3) / 3-(-5) (x+5)

y+3 = 6/8 (x+5)

y+3 = ¾ (x+5)

4(y+3) = 3(x+5)

4y + 12 = 3x + 15

3x-4y+3 = 0

Source(s): http://myrank.co.in/- Login to reply the answers

- Φ² = Φ+1Lv 71 month ago
(3--3)x - (3--5)y = 3×-5 - 3×-3 which is 6x - 8y = -6 which simplifies to 3x - 4y = -3.

Source(s): An equation of the line through the points (x₁,y₁) and (x₂,y₂) is (y₁-y₂)x - (x₁-x₂)y = y₁×x₂ - x₁×y₂- Login to reply the answers

- rotchmLv 71 month ago
Apply the exact same reasoning already given to you numerous times in:

https://ca.answers.yahoo.com/question/index?qid=20...

Show your steps here if need be & we then can further help you.

Hopefully no one will spoil you the answer thereby depriving you from your personal enhancement; that would be very inconsiderate of them.

- Login to reply the answers

- GTBLv 71 month ago
m = (y2-y1)/(x2-x1) = (3 - -3)/(3- -5) = 6/8 = 3/4

so y = (3/4)x + b and b therefore = y-(3/4)x and you enter the values of one ordered pair for x and y and you have b, you can do that; now you have the equation

- Login to reply the answers